PROTOTYPE PRODUK MAKANAN DESSERT ”CHEESECUIT” (STUDI KASUS PADA USAHA CHEESEECUIT D&E DI KOTA MAKASSAR) - Nurliani, Nurliani; Nurfadillah, Nurfadillah; Nuraeni, Nuraeni (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
Cheesecuit D&E is a micro business in Makassar that produces desserts made from cheese and biscuits. This study aims to create a prototype food product, a dessert, according to consumer needs and preferences. The research method used a qualitative descriptive approach, involving market surveys, identifying consumer needs and preferences, designing the product, and testing the prototype. The results showed that data and information were collected from a target market consisting of 27% males and 73% females, with an average age of 30 years and mostly students. The most preferred flavors were cheese and chocolate. The initial stage of developing the “cheesecuit D&E” dessert prototype involved conducting market surveys, designing the product, creating the initial product, conducting organoleptic tests, and finalizing the product. The product resulted in a product design that was in line with consumer preferences. Organoleptic tests showed a significant improvement in taste and visual aspects, especially for the cheese variant.